Association between Noise Intensity, Physical Workload, and Mental Workload with Work Stress among Workers at a Concrete Manufacturing Plant: A Cross-Sectional Study - Iwan Suryadi; Erwinda Alwi Rahman; Ni Luh Astri Indraswari; Antonius Budi Trianto; Nurlaila Fitriani (Media Kesehatan Politeknik Kesehatan Makassar, 2026)
The concrete industry is synonymous with high-pressure work environments, primarily from physical factors. This study aims to analyze the associated with of noise intensity, physical workload, and mental workload on work stress levels at PT Bosowa Beton, a modern concrete manufacturing plant. This research employed a cross-sectional design with 49 employees as respondents. Data were collected using the HSE Indicator Tool to measure work stress (where lower scores indicate higher stress levels), alongside the NASA-TLX for mental workload and Cardiovascular Load (CVL) for physical workload. Direct noise intensity measurements were conducted using a calibrated sound level meter. Data analysis was performed using correlation tests to identify relationships and associated with between variables. The average noise level was 86.54 dB (exceeding the TLV). A total of 18.4% of employees experienced high to very high stress. Statistical tests revealed that mental workload had a significant positive associated with on stress (p-value=0.041; r=0.293). Noise showed a significant negative relationship with stress (p-value=0.001; r=-0.459), while physical workload had no significant associated with stress (p-value=0.927; r=0.013). This finding indicates that the associated of stress originates from mental aspects. This study shows that mental workload and noise intensity are significantly associated with work stress, while physical workload is not. These findings highlight the importance of managing mental workload and controlling noise in the workplace. Further research using longitudinal or multivariate approaches is needed to clarify these relationships and develop more targeted interventions.